2018
DOI: 10.1039/c8ra00695d
|View full text |Cite
|
Sign up to set email alerts
|

MC4R variant rs17782313 and manifestation of obese phenotype in Pakistani females

Abstract: The current study significantly contributes to the knowledge of the genetic proneness to obesity in Pakistani females and could also be helpful for forthcoming meta-analysis studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 84 publications
2
10
1
1
Order By: Relevance
“…In some of our previous studies, we also reported genderspecific association of the other variants such as MC4R rs17782313, FTO rs9939609, and LEP rs7799039 with overweight/obesity and related anthropometric traits in Pakistani females (29)(30)(31). In comparison to these previously reported associations, the association of NEGR1 rs2815752 observed in the current study has a higher impact (effect size) but less strength.…”
Section: Discussioncontrasting
confidence: 70%
“…In some of our previous studies, we also reported genderspecific association of the other variants such as MC4R rs17782313, FTO rs9939609, and LEP rs7799039 with overweight/obesity and related anthropometric traits in Pakistani females (29)(30)(31). In comparison to these previously reported associations, the association of NEGR1 rs2815752 observed in the current study has a higher impact (effect size) but less strength.…”
Section: Discussioncontrasting
confidence: 70%
“…The evidence concerning this specific polymorphism that might contribute to overweight and altered feeding patterns is not limited to the populations mentioned above, but it has been also investigated and found in subjects of different nationalities and ethnic origins [ 147 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 ], where the majority of these studies addressed the vulnerability of women and children to moderate and severe obesity and aberrant eating behaviors [ 141 , 157 , 161 , 163 ].…”
Section: Melanocortin Receptors In Feedingmentioning
confidence: 99%
“…In our previous studies, the aforementioned individual associations were sought using multiple genetic models and in the case of obtaining association in more than one model, the h -index was calculated to indicate the relevant mode of inheritance (such as dominant, recessive, or over-dominant). Also, associations of the two variants FTO rs1421085 24 and TMEM18 rs7561317 25 were obtained without gender stratification while those of the other two namely MC4R rs17782313 23 and NEGR1 rs2815752 26 were observed after gender stratification in females only. Moreover, no association was found for BDNF rs6265 49 .…”
Section: Discussionmentioning
confidence: 90%
“…The current study computes the GRS based on the above-discussed five obesity-linked key loci ( FTO rs1421085, MC4R rs17782313, BDNF rs6265, TMEM18 rs7561317, and NEGR1 rs2815752), which were previously found to be individually associated with obesity and related anthropometric and metabolic measures in the same sample of Pakistani population 23 26 . In our previous studies, the aforementioned individual associations were sought using multiple genetic models and in the case of obtaining association in more than one model, the h -index was calculated to indicate the relevant mode of inheritance (such as dominant, recessive, or over-dominant).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation